Risk of secondary cancers in women with breast cancer and the influence of radiotherapy: A national cohort study in Taiwan. Issue 49 (December 2016) - Lin, Cheng-Yao; Chen, Sih-Hao; Huang, Chien-Cheng; Weng, Shih-Feng; Lee, Song-Tay; Guo, How-Ran; Kuo, Shu-Chun; Su, Shih-Bin
Abstract : Abstract: Breast cancer is the most common cancer in women worldwide; thus, the prolongation of survival, and the incidence and risk factors, including radiotherapy, for developing secondary malignancies are important. We compared the incidence of secondary and new primary cancers in women with breast cancer (CA Pos ) and well-matched for age, geographic region, and monthly income cancer-free controls (CA Neg ). The risk for secondary cancers with and without radiotherapy was also compared in CA Pos women. We enrolled 2422 CA Pos patients and CA Neg 12, 110 controls. In a 4-year follow-up, the secondary cancers risk was significant in the CA Pos group (adjusted hazard ratio [AHR]: 1.59; 95% confidence interval [CI]: 1.17–2.18). Only the risk of uterine cancer was significant compared with the controls (AHR: 6.30; 95% CI: 2.28–17.38). CA Pos patients and <50 years old had a higher risk for secondary cancers. Developing secondary cancers was significant in the first follow-up year (AHR: 1.51; 95% CI: 1.11–2.06). Radiotherapy had no significant effect on the CA Pos group, but it was significant ( P = 0.0298) in women ≥60 years old (elderly). We recommend monitoring secondary cancers in CA Pos women, especially those <50 years old, and during the first year of follow-up. Radiotherapy should be used more carefully in elderly CA Pos women.